Behavioral Leadership of Madrasah Principals Towards Improving Teacher Performance - Musyarofatus Sania Putri Wardoyo; Nurul Muayyadah; Mukhlishah Mukhlishah; Mardiyah Mardiyah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study is situated within the discipline of educational leadership, specifically focusing on the behavioural leadership perspective, which emphasises leaders’ observable actions in guiding and influencing their subordinates. The article aims to analyse how the behavioural leadership practices of the principal at MTS Salafiyah Syafiiyah Tebuireng Jombang contribute to improving teacher performance. Using a descriptive qualitative research design, data were collected through purposive sampling involving teachers as key informants, supported by non-participant observation and documentation study. Data analysis employed the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing, strengthened by source triangulation to ensure data validity. The findings reveal that the principal applies two core dimensions of behavioural leadership: task orientation and relationship orientation. Task orientation is reflected in structured instructions, systematic workflow arrangements, and consistent supervision of academic programmes, while relationship orientation appears in personal attention, open communication, and continuous moral support. These dimensions foster a supportive work climate, enhance teacher motivation, and strengthen professional commitment. These results underscore the significance of balanced behavioural leadership as an empirically grounded model for improving teacher performance and provide valuable insights for leadership development within Islamic educational institutions.